Pengaruh Customer Orientation dan Competitor Orientation Terhadap Sme Performance dengan Innovation Capability Sebagai Variabel Intervening pada UKM Furnitur Kayu di Jepara - Elsa Salsa Dila; Sari Listyorini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of customer orientation and competitor orientation on SME performance, with innovation capability as a mediating variable. A quantitative research approach was used, and data were collected using a questionnaire from 115 Small and Medium Enterprises (SMEs). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer orientation has a positive and significant effect on both innovation capability and SME performance. Competitor orientation also has a positive and significant effect on innovation capability and SME performance. Furthermore, innovation capability significantly influences SME performance. The mediation analysis reveals that innovation capability significantly mediates the relationships between customer orientation and competitor orientation on SME performance.These findings highlight the importance of market orientation and innovation capability in improving SME performance. The study implies that SME managers should strengthen both customer and competitor orientation while enhancing innovation capability to achieve sustainable competitive advantage and improved business performance.